IMPROVING THE QUALITY OF HEALTH SERVICES WITH THE IMPLEMENTATION OF PATIENT SAFETY EFFORT IN RENGEL PUSKESMAS - Surotul Ilmiah; Adibah Enggar; Esti Andarini (Fakultas Kesehatan, Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2022)
Background: Patient safety is one indicator of the quality of health services. Although patient safety incident data in first-level health care facilities are not yet accurate in Indonesia, patient safety is an important issue in improving service quality. Rengel Tuban Health Center is one of the health care facilities that implement patient safety efforts as a form of efforts to improve the quality of health services as referred to in the Law of the Republic of Indonesia Number 36 of 2009. Objective: The purpose of this study is to identify the application of patient safety efforts at the Rengel Tuban Health Center to improve service quality. Methods: The data collection techniques used were observation, interviews, and literature study. Data collection was carried out at the Rengel Tuban Health Center in January-February 2021. Results: The results of data analysis showed that the implementation of patient safety efforts at the Rengel Tuban Public Health Center was adjusted to the standards of the Puskesmas accreditation assessment. However, in its realization there are still obstacles and shortcomings in meeting patient safety standards at the Rengel Tuban Health Center so it is necessary to optimize the application of patient safety efforts from all parties involved. Conclusion: It can be concluded that puskesmas must provide safe and quality services to create a healthy subdistrict. Health centers need to improve patient safety in accordance with the Minister of Health of the Republic of Indonesia Number 36 of 2009